1991
DOI: 10.1002/ijc.2910490209
|View full text |Cite
|
Sign up to set email alerts
|

p53 Protein alterations in human testicular cancer including pre‐invasive intratubular germ‐cell neoplasia

Abstract: Expression of the p53 oncoprotein was examined in a wide range of primary human testicular germ-cell tumours using a new mouse monoclonal antibody (MAb) BP53-11 raised and characterized in this study, in parallel with a polyclonal rabbit antiserum CM-1. Immunohistochemistry on paraffin sections showed positive nuclear reaction in at least a fraction of malignant cells in 90 (84%) out of 107 cases studied. Aberrant accumulation of the p53 protein was found among testicular tumours of all major histological type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
2
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(50 citation statements)
references
References 29 publications
2
43
2
3
Order By: Relevance
“…The polyclonal CM-1 is a high-titre rabbit antiserum raised against full-length recombinant human p53 (Bartkova et al, 1991;Barton et al, 1991). It allows examination of formalinfixed, paraffin-embedded material and reacts with wild and most mutant forms of the p53 protein.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyclonal CM-1 is a high-titre rabbit antiserum raised against full-length recombinant human p53 (Bartkova et al, 1991;Barton et al, 1991). It allows examination of formalinfixed, paraffin-embedded material and reacts with wild and most mutant forms of the p53 protein.…”
Section: Antibodiesmentioning
confidence: 99%
“…Using a polyclonal antibody particularly effective in paraffins section, CM-1 (Bartkova et al, 1991;Barton et al, 1991), along with PAbl801 (Banks et al, 1986) and PAb240 Immunohistochemnistry Four micron paraffin sections were processed using the avidin-biotin complex (ABC) method (Vectastatin Elite kit, Vector, Burlingame, CA.) with diaminobenzidine tetrahydrochloride as the chromogen (Guesdon et al, 1979).…”
mentioning
confidence: 99%
“…To initiate studies of Chk2 in diverse organs and tumour types, we raised two mouse monoclonal antibodies against distinct epitopes of Chk2, and applied these as probes here to analyse Chk2 in human cultured cells, testicular tissues at various stages of development, and a range of germ-cell tumours. The reasons which led us to choose spermatogenesis and testicular cancer to study Chk2 include: (i) occurrence in the same tissue of both mitotic and meiotic cell cycles; (ii) high frequency of programmed DNA strand breaks as an essential part of genetic recombination during meiosis; (iii) a wellde®ned, early-stage common precursor lesion: carcinoma in situ (Skakkebñk et al, 1987); (iv) several types of GCTs, including teratomas capable of di erentiating along diverse cellular lineages (Chaganti and Houlds-worth, 2000); (v) male infertility in mice de®cient in either ATM (Barlow et al, 1997) or BRCA1 (Cressman et al, 1999) operating upstream or downstream of Chk2 in somatic cells, respectively; (vi) a possibility that testicular cancer is part of the Li-Fraumeni syndrome (Hartley et al, 1989); and (vii) the facts that p53, the immediate downstream target of Chk2, is involved in monitoring spermatogenesis (Rotter et al, 1993;Schwartz et al, 1999) and it is commonly overexpressed but not mutated in human GCTs (Bartkova et al, 1991;Chaganti and Houldsworth, 2000;Lutzker and Levine, 1996).…”
mentioning
confidence: 99%
“…It can also be frequently indicated by loss-of-heterozygosity which can be picked up by genotyping analysis (Mao et al, 2007). Bártková et al (1991) have demonstrated that altered expression of the p53 protein is a unifying feature of the majority of invasive male germ-cell tumors and that the change resulting in high levels of p53 appears to be a relatively early step in human testicular cancer pathogenesis. However, there are also some controversial opinions on the role of p53 in the development of testis cancer.…”
Section: Discussionmentioning
confidence: 99%